Pengaruh Karakteristik Perusahaan Terhadap Corporate Social Responsibility Disclosure - Aris Subranta; Gita Puspita; Rini Yulianti Putri (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Corporate Social Responsibility Disclosure (CSRD) has an important role for companies, because companies live in the midst of society. Each company has different factors that influence social responsibility disclosure even though the company is still in the same type of business. This research is intended to determine company characteristics that influence corporate social responsibility disclosure (CSRD) in the annual reports of companies in the Food and Beverage sector. The aim of this research is to find out whether company size as proxied by (SIZE), profitability as proxied by (ROA), and leverage as proxied by (DER) have an effect on CSRD. The sample used was 16 companies from 33 companies taken using purposive sampling technique. The results of this research are that there is a significant negative effect on company size, which is proxied by SIZE, on CSRD, profitability, which is proxied by ROA, and leverage, which is proxied by DER, has no effect on CSRD. And simultaneously company size, profitability and leverage influence CSRD in Food and Beverage sector companies listed on the Indonesia Stock Exchange in 2016 - 2020.